(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: The goal of this study is to use Design Expert Software to evaluate a transfersomal gel formulation for transdermal administration of Methotrexate utilising the Design of Experiments (DOE) Approach (Version 12, Stat- Ease Inc., Minneapolis, MN).Method: Transferosomes are ultra-flexible supra-molecular aggregates with a great ability to permeate intact mammalian skin. The formulation were designed by Box-Behnkenn Design by using Design Expert Software (Version 12, Stat- Ease Inc., Minneapolis, MN). For usage as a transferosomal gel, drug encapsulation in various transfersomal formulations having various ratios of different drug concentrations (0.05, 0.1, 0.2, 0.3, 0.4, 0.5 g) and Carbopol-940(0.5, 1.2 g) is being studied.Result: Optimized best formulation containing phosphatydylcholine and sodium deoxycholate ( 60:40:2)) was identified by Design Of Experiments® 12 software using Box-Behnkenn design exhibited particle size(125.7±0.05nm), entrapment efficiency(85.2±0.23%) and polydispersitivity index(0.245±0.31) and characterized the vesicles by Scanning electron microscopy and transmission electron microscopy shows stable vesicles. Ex-vivo permeation studies were performed by using goat skin showed good permeation. The transdermal flux of the Methotrexate loaded transferosomal gel is found to be 7.02±0.16 μg/cm-2/h at the end of 12th h.Conclusion: Transferosomes, according to this study, are a promising long-term delivery route for Methotrexate and are relatively stable. This research reveals that transferosomes containing Methotrexate could be used to treat Squamous Cell Carcinoma via transdermal drug delivery.